Intra- and Interlaboratory Reproducibility of an ELISA Serological Test for Lyme Disease - Martin C Tammemagi; John W Frank; Michael LeBlanc; Harvey Artsob (Canadian Journal of Infectious Diseases)
Objectives: Lyme disease has been increasingly diagnosed throughout North America since the late 1970s. The clinical diagnosis and epidemiological monitoring of Lyme disease are aided by serological testing for the etiological agent, Borrelia burgdorferi. Numerous authorities have questioned the reproducibility of these serological tests. This study assessed the intra- and interlaboratory reproducibility of an elisa used to aid in the diagnosis of Lyme disease.